2016
DOI: 10.5114/pjp.2016.61455
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of IgA-dominant postinfectious glomerulonephritis: a case report and review of the literature

Abstract: We report a case of IgA-dominant postinfectious glomerulonephritis in a 49-yearold man presenting with acute kidney injury, nephrotic range proteinuria and hematuria. He suffered from ischemic heart disease, cardiac insufficiency, mitral regurgitation, tricuspid insufficiency, septal aneurysm and hypertension. Renal biopsy revealed segmental and focal endocapillary and mesangial hypercellularity, and thickening of the glomerular capillary wall. Immunofluorescence showed co-dominant strong coarse granular immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
0
1
Order By: Relevance
“…Nevertheless, the association between diabetes and IRGN-IgA is inconstant, reported in 8 to 55 % of patients in previous studies and in 44 % of patients in our study. 10,12,[16][17][18][22][23][24] As seen since the first report, Staphylococcus represents the most frequent germ (78% in our study, 60 to 100% in other studies). 10,12,17,18,24 A higher frequency of MRSA was observed in Asian and American studies (50 to 60%) compared to our cohort (15%).…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, the association between diabetes and IRGN-IgA is inconstant, reported in 8 to 55 % of patients in previous studies and in 44 % of patients in our study. 10,12,[16][17][18][22][23][24] As seen since the first report, Staphylococcus represents the most frequent germ (78% in our study, 60 to 100% in other studies). 10,12,17,18,24 A higher frequency of MRSA was observed in Asian and American studies (50 to 60%) compared to our cohort (15%).…”
Section: Discussionsupporting
confidence: 73%
“…The initial description by Nasr et al reported diabetic nephropathy in all biopsies. Nevertheless, the association between diabetes and IRGN-IgA is inconstant, reported in 8 to 55% of patients in previous studies and in 44% of patients in our study [10,12,[16][17][18][22][23][24]. As seen since the first report, Staphylococcus represents the most frequent germ (78% in our study, 60 to 100% in other studies) [10,12,17,18,24].…”
Section: Discussioncontrasting
confidence: 51%
“…Cancer-related glomerulopathy can be differentiated from idiopathic glomerulopathy by considering several factors. For example, CAG is more common in older adults, while idiopathic glomerulopathy can occur at any age (3,5,20). Moreover, the presence of an underlying malignancy is a risk factor for developing CAG.…”
Section: Cag Versus Idiopathic Glomerulopathymentioning
confidence: 99%
“…The most common glomerular lesions that are caused by cancers is paraneoplastic glomerulopathy (4). Membranous nephropathy is the most common glomerular pathology associated with solid tumors (5). Various solid tumors, comprising lung cancers or renal cell carcinomas have been connected with vasculitis or rapidly progressive glomerulonephritis (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation